Structure–performance relationships of MnO2 nanocatalyst for the low-temperature SCR removal of NOX under ammonia. Issue 60 (8th June 2016) - Li, Yi; Li, Yanping; Wan, Yuan; Zhan, Sihui; Guan, Qingxin; Tian, Yang
Abstract : To investigate the corresponding relationship between catalytic efficiency and structure, MnO2 nanomaterials (nanospheres, nanosheets, nanorods) have been prepared successfully, and were thoroughly characterized by SEM and TEM. Abstract : To investigate the corresponding relationship between catalytic efficiency and structure, MnO2 nanomaterials (nanospheres, nanosheets, nanorods) have been prepared successfully, and were thoroughly characterized by SEM and TEM. Furthermore, the selective catalytic reduction (SCR) performance of NO X under ammonia was used as an indicative reaction. Among the MnO2 nanomaterials with different morphologies, it was found that their SCR activities showed an interesting variation tendency: nanospheres > nanosheets > nanorods of MnO2 . The NO conversion ratio of the MnO2 nanospheres could reach 100% from 200 to 350 °C. Moreover, in order to study the probable mechanism for the best removal efficiency of the nanospheres, XRD, H2 -TPR, NH3 -TPD, BET, XPS and in situ DRIFTS were performed in detail. It is found that surface chemisorbed oxygen, specific surface area, reducibility and acid sites have great influence on the NO removal efficiency in the SCR reaction. In addition, how several process parameters affect the NO X removal efficiency was carried out, such as time, H2 O and SO2 .